Influence of Selected Factors on Penetration and Drying Kinetics of Protective Coatings into Sand Mould Surface Layer - Ł. Jamrozowicz (Archives of Foundry Engineering)
This paper presents the results of measuring moisture migration in the surface layer of a sand mould during the soaking and drying processes of protective coatings. In the introduction, the process of moisture exchange between the surroundings and the moulding sand is briefly introduced, and the flow of moisture in porous materials is presented. Since the aim of the research is to understand the mechanism of the penetration and drying processes of a protective coating that is applied to a core or mould, the purpose of protective coatings and the consequences of poor drying are presented. During the research, a novel test rig was used to measure the resistance of a porous medium due to moisture migration. An alcohol-based zirconia coating with a conventional viscosity of 20 s was used for the tests. The viscosity of the coating was determined by using a Ford cup with a mesh clearance of 4 mm. The cores for the tests were made from a phenol-formaldehyde resin moulding compound. The average grain size of the sand matrix was dL = 0.25 mm. During the core preparation, pairs of electrodes were placed in the mass at depths of 1, 2, 3, 4, 5, 8, 12, 16, and 20 mm. The resistance was measured continuously. During the tests, the moisture-migration process in the top layer of the core was determined after the protective coating was applied to it. The tests were conducted in a climatic chamber with air temperatures of T = 25° and 35°C and humidity levels of H = 39 and 80%.